The truth about testing : an educator's call to action - Popham, W. James. 4 0 16; 5 (Alexandria, Virginia : Association for Supervision and Curriculum Development, 2001)
Discusses good and bad student testing, shows teachers how to construct accurate methods of assessment and use their results to teach, and explains how teachers can protect themselves and students by educating parents, policy makers, and others about what kinds of testing are effective.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Standards -- Educational tests and measurements;Education -- United States.;United States. -- 20; 20; 2